2021
DOI: 10.1016/j.ijdrr.2021.102109
|View full text |Cite
|
Sign up to set email alerts
|

Medical students as the volunteer workforce during the COVID-19 pandemic: Polish experience

Abstract: In response to the COVID-19 pandemic medical students in different countries were mobilized to support healthcare systems during the emergency. This study presents the experience of 580 students of a single medical university in Poland who served as volunteers at different healthcare units during the first six months of the first case being recorded in the country (March-September 2020). The mean±SD hours and days spent on volunteering in the studied group were 52±36 and 144±126, respectively, the collective n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
100
1
19

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(131 citation statements)
references
References 45 publications
11
100
1
19
Order By: Relevance
“…Their motivation was accounted for by Clary and Snyder [ 18 ] as six personal and social functions that can be applied to other volunteering contexts in various crisis situations: (1) increasing expression of values such as altruism, (2) seeking learning opportunities and experiences to understand world-views during health crises, (3) enhancing personal growth and psychological development, such as through the fulfillment of their calling and passion pursuit, (4) gaining career-related clinical skills and experiences, (5) fortifying social relationships with peers and beneficiaries (e.g., migrant workers), and (6) protecting oneself from feeling bored, purposeless and guilty for not helping. As is consistent with observations made by our lecturers, Bazan et al [ 19 ] reported that Polish medical students characterized by curious, sensitive, calm, and sociable personalities were more likely to volunteer. Individuals with such traits, linked to extraversion, agreeableness, and openness, have more salient helping identities, and are associated with a greater propensity to volunteer [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…Their motivation was accounted for by Clary and Snyder [ 18 ] as six personal and social functions that can be applied to other volunteering contexts in various crisis situations: (1) increasing expression of values such as altruism, (2) seeking learning opportunities and experiences to understand world-views during health crises, (3) enhancing personal growth and psychological development, such as through the fulfillment of their calling and passion pursuit, (4) gaining career-related clinical skills and experiences, (5) fortifying social relationships with peers and beneficiaries (e.g., migrant workers), and (6) protecting oneself from feeling bored, purposeless and guilty for not helping. As is consistent with observations made by our lecturers, Bazan et al [ 19 ] reported that Polish medical students characterized by curious, sensitive, calm, and sociable personalities were more likely to volunteer. Individuals with such traits, linked to extraversion, agreeableness, and openness, have more salient helping identities, and are associated with a greater propensity to volunteer [ 20 ].…”
Section: Discussionsupporting
confidence: 93%
“…In the United Kingdom, the hospitals have successfully integrated medical students into nursing teams (4). The experiences of the COVID-19 pandemic in Poland have shown that medical students who have worked voluntarily in frontline health services reported a low level of fear and received positive feedback from family, friends, patients, and healthcare workers (5). In the US, medical students can deploy to local health agencies to implement rapid testing, join student outbreak response teams, implement critical preventive policies, or be staff of community call centers that offer guidance and services to individuals with symptoms of or exposed to COVID-19 (6).…”
Section: Introductionmentioning
confidence: 99%
“…In the fight against the COVID-19 virus, medical students from different countries participated as volunteers in supporting the health system. According to a study conducted in Poland [16], the volunteer activities of medical students included triage activities, call-center service for patients, working in hospitals and clinical laboratories. The volunteer students received positive feedback from patients, families, friends, as well as from healthcare personnel.…”
Section: Resilience Of Education In the Covid-19 Pandemicmentioning
confidence: 99%